A study on the effectiveness of display at tableware department at living quarters Bandar Utama / Ungku Azhar Ungku Elias - Ungku Elias, Ungku Azhar (1999)
The study of the effectiveness of the display is necessary for every retailer because from that they can know current performance of the company and how to improve it. It also can know how customer perceive the product offered in term of quality, price and material used towards the display. This information gathered may help LIVING QUARTERS to improve customer service in order to give effective serve to t heir customers in the future. The objective of this study is to gain information and knowledge regarding the effectiveness of the display at the tableware department in LIVING QUARTERS Bandar Utama From this study it can identify problems and some recommendation can be recommend to improve the outlet sales and customer flows.